Prevalence and factors associated with potential drug interactions among elderly in a population-based study - Gotardelo, Daniel Riani (2014)
Objectives: The aim of this study was to determine the prevalence of potential drug interactions and the factors associated with them among elderly patients covered by the Family Health Strategy in the municipality of Timóteo, state of Minas Gerais, Brazil. Methods: Cross-sectional study, using stratified random sampling. A total of 273 household interviews were conducted in subjects aged 60 years or older, after obtaining informed consent, using a questionnaire containing questions related to identification, demography, health conditions and medication use. Drug interactions were identified and classified according to the software Micromedex®. Results: The overall prevalence of potential drug interactions was 55.6%, a total of 466 cases, of which 5.6% were mild, 81.6% moderate and 12.8% of greater severity. Therapeutic classes most frequently involved were anti-inflammatory drugs and especially drugs used in cardiovascular disease. The absence of hospitalization in the last four months was significantly associated with a lower chance of serious drug interactions and most patients who did not have any moderate drug interactions used only drugs prescribed by physicians. Conclusions: The prevalence of potential drug interactions was similar to that described in the literature, demonstrating the high frequency of this phenomenon among the elderly. The absence of prior hospitalization and drug prescription by physicians were associated with a lower frequency of interactions. The prescription of multiple drugs simultaneously to elderly patients can compromise the safety and health of this population, requiring, by caregivers, observation for the occurrence of potential drug interactions.